Metagenome-derived draft genome sequence of acidithiobacillus ferrooxidans RV1 from an abandoned gold tailing in neuquén, Argentina - Ulloa, José Ricardo (2017)
In this work we report the metagenome-derived draft genomic sequence of an enrichment culture dominated by A. ferrooxidans obtained from an airlift bioreactor inoculated with the microbial consortium recovered from the “Relave Viejo” tailing. The genome of this culture was assembled de-novo and by reference, generating a consensus assembly of 3.0 Mb. On the basis of 16S rRNA (100 % identity), average nucleotide identity analysis (99.33% identity) and in silico DNA-DNA hybridization against A. ferrooxidans ATCC 23270T (97.9%), the recovered genome is confirmed to pertain to A. ferrooxidans species. Comparative genomics results are presented to uncover the genetic traits of the variant surviving lime treatment and to further explore the genomic diversity of these model iron oxidizing species.